EVALUATION OF POTATO-BASED CROP SEQUENCES FOR UPLAND CULTIVATION IN ASSAM - Saikia, Mrinal; Helim, R.; Thakur, K C; Naik, P S (Potato Journal, 2013)
Four potato-based cropping sequences were evaluated at Jorhat (Assam) during 2002-03 and 2003-04 for determining productive efficiency and economic profitability under upland situations of Assam. Among different crop sequences, potato-okra-black gram was the best followed by potato-groundnut-green gram with highest potato equivalent yield, production efficiency and land use efficiency.